High School MMORPG (Massively Multiplayer Online Role-Playing Game) Players: Profile, Collaborative Behavior, and Empathy - Tobias-Domagsang, Anne Gelene; Campoamor-Olegario, Lizamarie (Alipato, A Journal of Basic Education; Vol 13 (2022), 2023)
There has been a rise in the number of high school students getting hooked on Massively Multiplayer Online Role-Playing Games (MMORPG). At present, there are 3.03 billion gamers worldwide, about 28.72 million of them are Filipino MMORPG players and 48% are between the age group of 13-17 years old (“Online gamers in the Philippines 2022,” 2022a). Because MMORPGs are games in which players compete in teams this research focuses on them to look at whether collaborative behavior and empathy are present in the individuals who play the game in face-to-face settings. The research utilized the mixed-method explanatory design to determine this. Three sets of questionnaires measuring gaming habits, motivation, and adolescent empathy quotient were administered to 378 high school MMORPG players in Quezon City. Face-to-face collaborative classroom activities were conducted among 30 selected high school gamers and their collaborative behavior was assessed by five teacher-observers. Focus group discussions (FGD) with the students and interviews with the teachers and parents were also conducted. The MMORPG gamers were found to have early and high levels of exposure to online gaming, proficient collaborative skills, and low empathy. There was no significant relationship between collaborative behavior and empathy.